2014
DOI: 10.1039/c3sc52943f
|View full text |Cite
|
Sign up to set email alerts
|

A series of C3-symmetric heterobimetallic Cr–M (M = Fe, Co and Cu) complexes

Abstract: A series of tris(phosphinoamide) heterobimetallic Cr-M (M ¼ Fe, Co and Cu) complexes has been investigated in an effort to probe and contribute to the understanding of the electronic structure and metal-metal bonding in heterobimetallic complexes of the first row transition metals. The chromium tris(phosphinoamide), [Cr( i PrNPPh 2 ) 3 ] (1), is a useful isolable precursor and can be treated with MI 2 under reducing conditions to form [Cr( i PrNPPh 2 ) 3 M-I] (M ¼ Fe (2), Co (3)). Both of these complexes can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 42 publications
8
57
0
1
Order By: Relevance
“…To best describe the magnetic data presented in the previous section, two models were employed: (1) a single spin (SS) model that considers the six-metal-atom cluster to behave as a single-spin entity, as has been done previously, 11a,45 and (2) a coupled spins (CS) model that assumes the spins of metal sites within the cluster to be coupled. In the latter model, the iron sites are coupled through exchange interactions between adjacent ( J cis ) and trans-located ( J trans ) metal sites.…”
Section: Resultsmentioning
confidence: 99%
“…To best describe the magnetic data presented in the previous section, two models were employed: (1) a single spin (SS) model that considers the six-metal-atom cluster to behave as a single-spin entity, as has been done previously, 11a,45 and (2) a coupled spins (CS) model that assumes the spins of metal sites within the cluster to be coupled. In the latter model, the iron sites are coupled through exchange interactions between adjacent ( J cis ) and trans-located ( J trans ) metal sites.…”
Section: Resultsmentioning
confidence: 99%
“…Kempe et al reported a few Nd-Rh and Nd-Pd complexes about 15 years ago. Co-Ti, 11 Co-Zr, 10,12 Co-Hf, 3 Pt-Zr, 13 V-Fe, 14 Nb-Co, 5b Ta-Co, 5b and Co-U. Hou et al recently published rare-earth-platinum heterobinuclear half-sandwich rare-earthmetal alkyl complexes bearing Cp ligands with a phosphine side arm.…”
mentioning
confidence: 99%
“…Cr/Ir complexes from treatment of the previously reported Cr tris(phosphinoamide) complex Cr( i PrNPPh 2 ) 3 [10] with [MCl(COD)] 2 precursors have proven unsuccessful thus far. Therefore, we turned our attention to a more electron-rich chromium variant, namely Cr( i PrNP i Pr 2 ) 3 (1).…”
Section: Synthesis and Structural Characterization Of 1-3 Attempts Tmentioning
confidence: 99%
“…In recent years, heterobimetallic complexes have seen a resurgence in the literature, with the emergence of chelating ligand platforms carefully designed to hold two different metal centers in close proximity. The Thomas and Lu groups, in particular have utilized C 3 -symmetric ligand platforms with the appropriate combination of hard and soft donor ligands to support both early/late heterobimetallic complexes and homobimetallic complexes with coordination site differentiation [7][8][9][10][11][12][13][14]. By targeting complexes featuring first row metals, the systematic variation of metal-metal combination, redox state, and ligand environment has provided a better understanding of the metal-metal bonding in heterobimetallic complexes [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation